ANALISA KETERKAITAN ANTARA INDIKATOR, TUJUAN PEMBELAJARAN, MATERI PEMBELAJARAN DAN EVALUASI DALAM RENCANA PELAKSANAAN PEMBELAJARAN (RPP) GURU MATA PELAJARAN BIOLOGI SMP NEGERI DAN SWASTA DI KOTA PADANG - Nurianti, Efri; Mulyati, Mulyati; Risdawati, Renny (Pendidikan Biologi, 2013)
ABSTRACT             Succes or failure of a teacher in study process influenced by many factor, one of amongs use how the lesson plan (RPP) make or the designed by teacher before study which process this research purpose to know related between indicator with a purpose to study, the purpose of study with material of study and the purpose of study with evaluation of study in lesson plan (RPP) compiled by teacher in the first public high school and Private secondary school in Padang City.Result of research shown in the first public high school criterion relevant between indicator with purpose of study very related equal to 83,12 %, the relevant of purpose of study with material of study very related equal to 90,57%, and relevant between purpose of study with evaluation of study enough related equal to 53,20%. Private secondary school in criterion relevant between indicator with purpose of study very related equal to 89,45%, the relevant of purpose of study with material of study very related equal to 87,06%, and relevant between of purpose of study with evaluation of study enough related equal to 47,61%. The conclusion relevant between indicator with learning purpose, learning purpose with learning material. So relevant, and learning purpose with evaluation is relevant.